Dramas e tramas do (não) aprender: significações sobre o sujeito que apresenta dificuldades de aprendizagem - Nascimento, Rita de Cássia Souza (2007)
This research aimed to investigate and to comprehend the meanings constructed by teachers, parents and students on the ones who present learning difficulties and their interrelationships in the constitution of the me and of the other , using the historical-cultural perspective as the theoretical approach. This interest forms a comprehension process of ties occurring in practices of each context. The meanings mark the student s condition of not being able to learn, turning this situation into a drama of (not) learning. Two (02) children enrolled in elementary schools (1st to 4th grades) who were diagnosed with learning difficulties, as well as their mothers and teachers were individually interviewed for 40 minutes. From their talks, we identified three (3) blocks with themes: children and (not) learning, others (mothers, teachers/school) and (not) learning and the reasons of (not) learning. Concerning the self and (not) learning, the participants presented reasons as: the children believe that they cannot learn; possess a feeling of self depreciation; the way the other look upon them weighs heavily on their identity and they even say that the difficulty in learning is their own; the mothers: suffer due to their children s condition and over all for not being able to deal with the situation; show worry, sadness, unsatisfaction and even, impotence and lack of knowledge on their children s learning; the teachers: desperation, discouragement, affliction and concern. The teachers were asked about their own teaching activities and the lack of comprehension on children in their reality and in their singularity as well as the need of theoretical knowledge were identified. Concerning the other , mothers perceive their children as sad because of the learning difficulty and also they believed that their children are not able to learn. Besides sentiments of sadness, teachers believe that students also feel incompetent and even ashamed for not being capable of learning. Among of the motives for not learning, we identified organic, genetic, pedagogic, affective aspects and factors that obstruct that process such as the lack of schooling in the family or the lack of psychological orientation service and the ignorance on students learning difficulties in school contexts. The results of this study proved that this work impels toward the necessity of understanding this drama of (not) learning where meanings have been produced and marked the student who presents learning difficulties. However, this drama represents a situation of conflict in which students, teachers and parents are inserted and which is considered, therefore, an aspect that impels professionals acting in education improvement who in turn needs to comprehend this interrelationship and this dramatic condition that involves the school community.